Food intake survey of kindergarten children in Korea: Part 2 increased dietary intake of tin possibly associated with canned foods - Yang, Hye-Ran (Environ Health Prev Med, 2015)
OBJECTIVES: Dietary intake of tin (Sn) may be increased in some children in kindergartens in Korea. The present study was intended to examine this possibility and clarify the extent of the elevation. METHODS: 24-hour food duplicate and spot urine samples were collected in 2003–2004 from 108 4–6-year-old children (boys and girls combined) in 4 kindergartens (1 in Seoul and 3 in Jeju Island), as reported in a previous publication. These samples were employed in the present analyses to examine tin levels in the diet (including beverages) (Sn-D). A portion of the samples were wet-ashed, and the liquid samples were analyzed for Sn by the ICP-MS method. For statistical evaluation, χ(2) method and Smirnov’s test for extreme value were used. RESULTS: Sn-D in the 108 cases distributed as extremely biased, and could be divided into two groups, i.e., those with <10 μg Sn/day (accounting for 90 % of the cases), and those with >10 μg/day (for 10 %). Sn-D in the former group was distributed quasi-normally with an AM (median) of 2.9 (2.5) μg/day. The maximum in the latter group was 3012 μg/day. No correlation was detected between Sn-D and Sn in urine (Sn-U). Comparison of the findings with published articles strongly suggested that the high Sn-D was due to consumption of foods (including beverages) preserved in tin-plated cans. No positive confirmation was however possible due to insufficient information on food records. CONCLUSIONS: About 10 % of children surveyed had elevated Sn-D (up to 3 mg/day). It was quite possible that high Sn-D was associated with tin-canned food intake.